(untitled) - Cruickshank, Donald R. (Boston, 2006)
Designed for the general methods course, this renowned text provides the broadest content coverage related to understanding oneself as a teacher. It provides understanding of one's students and how they learn, and understanding of what is known about the act of teaching. This book contains the most up-to-date knowledge base about the teaching profession. In its second edition, The Act of Teaching continues to provide students with the explicit, step-by-step guidance needed to get them up-and-running as practitioners of the most commonly used teaching strategies: presentation, discussion, independent study, cooperative learning, discovery learning, direct instruction, and individualized instruction. In addition, it provides thorough and up-to-date coverage of such major topics as instructional planning, maintaining time-on-task, monitoring, questioning, assuring clarity, classroom management and assessment, and providing reinforcement and corrective feedback.
Keywords: Teaching,Lesson planning